2021
DOI: 10.1016/j.jshs.2020.12.003
|View full text |Cite
|
Sign up to set email alerts
|

The epigenetic landscape of exercise in cardiac health and disease

Abstract: Highlights Exercise induces a profound alteration in epigenetics, which mediates the beneficial effects of exercise. Exercise not only modifies epigenetics in the heart to promote cardiac health, but also modifies epigenetics in other tissues, which reduces risks of cardiac disease or affords cardioprotection through exerkines. Exercise-modulated circulating non-coding RNAs are secreted from multiple tissues and shuttled by exosomes, acting as a new kind o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 124 publications
0
16
0
1
Order By: Relevance
“…Recent studies have identified exerkines, which are secreted from multiple tissues in response to exercise, as major players in orchestrating cell-to-cell crosstalk and mediating the exercise-induced beneficial effects. 12 , 13 , 14 Among exerkines, myokines, including interleukin 6, irisin, and apelin secreted from skeletal muscles, have been studied extensively. 15 , 16 Searching for exerkines provides a framework for understanding how exercise mediates many of its beneficial effects and provides a platform for pharmacotherapy development in various diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have identified exerkines, which are secreted from multiple tissues in response to exercise, as major players in orchestrating cell-to-cell crosstalk and mediating the exercise-induced beneficial effects. 12 , 13 , 14 Among exerkines, myokines, including interleukin 6, irisin, and apelin secreted from skeletal muscles, have been studied extensively. 15 , 16 Searching for exerkines provides a framework for understanding how exercise mediates many of its beneficial effects and provides a platform for pharmacotherapy development in various diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it is unclear whether RNA modifications, such as m6A methylation, are also affected by the abovementioned risk factors. In addition, exercise is a non-pharmacological intervention that can alleviate CMDs and directly change the epigenetics of the heart, thereby promoting cardiovascular health and protecting the heart from various pathological processes [ 101 ]. However, it is unclear whether exercise changes the phenotype of CMDs by regulating the level of m6A methylation and specifically affecting the downstream targets and signaling pathways of m6A methylase and demethylase.…”
Section: Conclusion and Prospectivementioning
confidence: 99%
“…RNA, ncRNA)的表达, 这些ncRNAs可在细胞内发挥生 物学效应, 也可分泌至细胞外调节临近或远隔细胞的 功能 [77,78] . 近年愈来愈多的研究显示, 运动可通过 ncRNAs发挥心血管保护作用.…”
Section: 运动可影响多种组织非编码Rna(non-codingunclassified